4D UTE flow: A phase‐contrast MRI technique for assessment and visualization of stenotic flows. Issue 3 (6th March 2014) - Kadbi, Mo; Negahdar, MJ; Cha, Jung won; Traughber, Melanie; Martin, Peter; Stoddard, Marcus F.; Amini, Amir A.
<x xml:space="preserve">Abstract</x> Purpose Inaccuracy of conventional four‐dimensional (4D) flow MR imaging in the presence of random unsteady and turbulent blood flow distal to a narrowing has been an important challenge. Previous investigations have revealed that shorter echo times (TE) decrease the errors, leading to more accurate flow assessments. Methods In this study, as part of a 4D flow acquisition, an Ultra‐Short TE (UTE) method was adopted. UTE works based on a center‐out radial k‐space trajectory that inherently has a short TE. By employing free induction decay sampling starting from read‐out gradient ramp‐up, and by combining the refocusing lobe of the slice select gradient with the bipolar flow encoding gradient, TEs of ≈1 msec may be achieved. Results Both steady and pulsatile flow regimes, and in each case a range of Reynolds numbers, were studied in an in‐vitro model. Flow assessment at low and medium flow rates demonstrated a good agreement between 4D UTE and conventional 4D flow techniques. However, 4D UTE flow significantly outperformed conventional 4D flow, at high flow rates for both steady and pulsatile flow regimes. Feasibility of the method in one patient with Aortic Stenosis was also demonstrated. Conclusion For both steady and pulsatile high flow rates, the measured flow distal to the stenotic narrowing using conventional 4D flow revealed more than 20% error compared to the ground‐truth flow. This error was reduced to less than 5% using the 4D UTE flow technique. Magn Reson Med 73:939–950, 2015. © 2014 Wiley Periodicals, Inc.